PELINDUNGAN PETUGAS MEDIS DAN KEMANUSIAAN DALAM KONFLIK BERSENJATA BERDASARKAN GENEVA CONVENTION FOR THE AMELIORATION OF THE CONDITION OF THE WOUNDED AND SICK IN ARMED FORCES IN THE FIELD OF 12 AUGUST 1949 (KONVENSI JENEWA I TAHUN 1949) - Dwianto, Aditiya Rizki; Deliana, Evi; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Definitively, war / armed conflict is the highest condition of a form of conflict between people. As a result of armed conflict in several studies mention that in humans there is an instinct to injure or attack, so it takes the limitations and regulations regarding the laws of war or what is known today is humanitarian law. the main purpose of humanitarian law is to provide protection to those who suffer / become victims of war, both those who are actually / actively participating in hostilities (combatants) or not participating in hostilities (civilians / non-combatants), including medical officers and volunteers humanity. In fact, the protection of medical personnel and humanitarian volunteers in an armed conflict or war is very difficult to guarantee and implement in an ideal and consistent manner in accordance with the provisions of the law. Whereas medical workers and humanitarian volunteers should have guaranteed protection.This research uses the typology of normative legal research, which more specifically discusses the principles of law. In this study the authors use the nature of descriptive research, because the authors describe the protection under the Geneva Convention of the Amelioration of the Condition of the Wounded and Sick in Armed Forces in the Field of 12 August 1949 (Geneva Convention I of 1949) in protecting Medical Officers during Conflict Armed. The results of the research conducted by the author are, firstly the position as medical and humanitarian officers in armed conflict is included in non-combatants. The position of medical and humanitarian officers has been protected by the Geneva Conventions. Geneva law protects medical personnel and humanitarian volunteers in all circumstances, but in return, they must also be neutral. Second, the form of protection for medical officers and humanitarian volunteers is something that is considered a general rule in war. Third, based on the National Mechanism According to the Geneva Conventions of 1949 and the Additional Protocol of 1977, namely the enforcement of Humanitarian Law which is implemented based on a national judicial process. That is, if there is a case of violation of humanitarian law, the perpetrator will be prosecuted and punished based on national legislation and by using the relevant national justice mechanism. Based on the International Criminal Court, which can only be implemented if it turns out a country is unwilling and unable (Unwilling and Unable) to prosecute crimes that fall within the scope of the competence of the International Criminal Court.Keywords: Protection - Medical Officers - Humanitarian Volunteers – Armed Conflict - Geneva Convention.